Cobalt‐Embedded Nitrogen‐Doped Carbon Nanotubes as High‐Performance Bifunctional Oxygen Catalysts. Issue 8 (20th February 2017) - Hao, Yongchao; Lu, Zhiyi; Zhang, Guoxin; Chang, Zheng; Luo, Liang; Sun, Xiaoming
Abstract: The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are key processes in various renewable‐energy technologies and call for high‐performance bifunctional ORR/OER electrocatalysts. In this study, a highly efficient bifunctional oxygen catalyst, which was made of bamboo‐like nitrogen‐doped carbon nanotubes with embedded cobalt nanoparticles (Co@NCNTs), was fabricated by a one‐step pyrolysis route. Systematic electrochemical results demonstrated that the optimized electrocatalyst only needed a small potential hysteresis of about 0.834 V to achieve 1 mA cm −2 ORR current and 10 mA cm −2 OER current, and simultaneously gave superior stability and methanol tolerance to those of commercial metal catalysts. The major factors that influenced the bifunctional catalyst performance of Co@NCNTs are discussed, among which the nitrogen chemical state and metal element play important roles. Moreover, the catalyst showed good activity and stability in rechargeable zinc–air batteries, which indicated their potential applications in metal–air batteries, fuel cells, and water‐splitting devices. Abstract : Two catalysts in one : A highly efficient bifunctional oxygen catalyst composed of bamboo‐like nitrogen‐doped carbon nanotubes with embedded cobalt nanoparticles (Co@NCNTs) is investigated. The major factors that influence the bifunctional catalyst performance of Co@NCNTs are discussed, among which the nitrogen chemical state and metal element play important roles.